Blood Glucose Alterations in Spinal versus General anesthesia in those undergoing Cesarean Section Delivery - Alireza Manafi; Habibollah Zakeri; Fatemeh Salahyan; Marzieh Tavassoli; Fahimeh Shekoohi; Roya Kokabi; Sahar Khazforoosh (Fasa University of Medical Sciences, 2015)
Introduction: Major body injury or surgery is associated with reproducible metabolic and hormonal responses. Alteration of blood glucose levels is one of the necessary metabolic changes to surgical stress. Surgical techniques and different methods of anesthesia are factors that can help to control and balance the body's hormones. One of the most effective ways for decline the endocrine-metabolic response is local anesthesia. We conducted this study to compare the measurement of blood glucose before, during and after surgery and complete the pieces of anesthesia puzzle. Methods & Materials: This was retrospective cohort study performed on 126 patients between 18-38 ages under cesarean section. Sixty-three women who were undergoing spinal anesthesia have been selected as first group, and the second group was 63 patients with general anesthesia. In this study, level of glucose was recorded by glucometer 30 min before surgery (in waiting room), during operation (after childbirth) and 30 min after surgery (in recovery room) measured and recorded. Results: Average of blood glucose levels in spinal anesthesia group was significantly different between the three measurements (p value = 0.007), and also in the general anesthesia group were more significant (p value < 0.001). Mean of blood glucose 30 min before surgery in spinal and general anesthesia, were 81.49±14.64 and 84.09±10.95, respectively (p value = 0.26), and during surgery were 86.50±23.49 and 90.74±17.82 (p value = 0.256), and finally 30 min after operation were 79.93±18.35 and 94.87±16.32 ( p value < 0.001). Conclusion: Spinal anesthesia is more effective way to decease blood sugar alterations and its adverse effects on mothers hormonal system during cesarean sections.